2023
DOI: 10.1039/d3py00138e
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble polymers with aggregation-induced emission and ultra-long room temperature phosphorescence

Abstract: Polymer-based pure organic room-temperature phosphorescent materials have attracted much attention from researchers due to diverse molecular design, favorable processibility, good flexibility and potential applications in flexible electronics, anti-counterfeiting and information...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Room-temperature phosphorescence (RTP) materials play a pivotal role in bioimaging, anticounterfeiting, information encryption, optical displays, and chemical detection. At present, most RTP materials are precious metals, rare element–containing inorganic materials, or organic–inorganic complexes and are associated with high costs, high toxicity, low processability, and difficult fabrication processes, hindering their practical applications. In recent years, several studies have reported that certain natural products, such as cellulose, maltose, agarose, and sodium alginate, without a well-defined chromophore or conjugated structure exhibit fluorescence or/and RTP in concentrated solution or solid-state conditions. These molecules usually contain heteroatom groups (groups containing, e.g., N, O, and S) and exhibit concentration-dependent fluorescence and excitation-dependent emission.…”
Section: Introductionmentioning
confidence: 99%
“…Room-temperature phosphorescence (RTP) materials play a pivotal role in bioimaging, anticounterfeiting, information encryption, optical displays, and chemical detection. At present, most RTP materials are precious metals, rare element–containing inorganic materials, or organic–inorganic complexes and are associated with high costs, high toxicity, low processability, and difficult fabrication processes, hindering their practical applications. In recent years, several studies have reported that certain natural products, such as cellulose, maltose, agarose, and sodium alginate, without a well-defined chromophore or conjugated structure exhibit fluorescence or/and RTP in concentrated solution or solid-state conditions. These molecules usually contain heteroatom groups (groups containing, e.g., N, O, and S) and exhibit concentration-dependent fluorescence and excitation-dependent emission.…”
Section: Introductionmentioning
confidence: 99%